العدوى الكامنة بالسلمونيلات عند الدواجن كمصدر للتسمّمات الغذائية عند الإنسان - نيصافي علي; عبد العزيز فهيم (Latakia University Journal -Biological Sciences Series, 2018)
كان هدف البحث الحالي كشف الإصابة الكامنه بالسلمونيلة الدجاجية بللوروم والسلمونيلة الملهبة للأمعاء والسلمونيلة التيفية الفأرية عند أنواع مختلفة من الطيور المختبرة في منطقة البحث، والمساهمة في تقصي العملية الوبائية لهذه السلمونيلات وإثبات وجود الثوي الخازن أو الحامل لها والتنبه إلى الأهمية الخاصة لهذه الطيور ودورها في نقل العدوى والتسممات للإنسان. أجريت فحوص مصلية سريعة (اختبار النقطة ) ل 3540 عينة من طيور أهلية شملت هجن تجارية من الفروج ومن الدجاج البياض والدجاج المنزلي وكذلك طيور حمام وبط وإوز وحبش (رومي) ودجاج فرعون متوزعة في مناطق مختلفة من الساحل السوري. أظهرت نتائج هذه الفحوص وجود إصابة كامنة بالسلمونيلة الدجاجية بللوروم عند الدجاج المنزلي فقط، بينما أثبتت الإصابة بالسلمونيلة الملهبة للأمعاء عند كل من الدجاج المنزلي والحمام والحبش والبط , وبينت خلو الإوز من الإصابة بكلا النوعين . كما أثبتت نتائج الفحص إيجابية العينات المختبرة من الدجاج والحمام والبط فقط مقابل السلمونيلة التيفية الفأرية ولم ينفذ الاختبار الأخير على الطيور الأخرى. وبين إحصاء نتائج تفاعل فيدال لتشخيص الحمى التيفية عند الإنسان تسجيل حالات إيجابية بنسبة 2,6%. ويستنتج من ذلك أن تواجد هذه الطيور ومعيشتها في بيئة الإنسان والحيوان يجعل الفرصة مهيأة لانتقال السلمونيلة إليهما بما تسببه من تسممات وأمراض مختلفة لذلك يجب تركيز الانتباه على هذا النوع من العدوى واتخاذ التدابير الكفيلة بالوقاية منها ويلعب البحث الحالي دورا هاما في هذا المجال وفي تتبع وتقصي العملية الوبائية لهذا المرض. The purpose of the current research was to detect latent infection in poultry salmonella pullorum, salmonella enteritides, and salmonella typhimurium in various kinds of birds examined in the research area, to contribute in investigating the epornitic process of these salmonellae and demonstrate the presence of their storing host or vector and be aware of the particular importance of these birds and their role in transmitting infection and toxicities to man. Quick serous tests (dot test) were made on a sample of (3540) domestic birds, which included commercial hybrids of chicken, egg laying hens, domestic hens as well as pigeons, ducks, geese, guinea fowls (turkeys), and Pharaoh Hens distributed in several regions of the Syrian Coast. Results of these tests revealed the existence of latent poultry salmonella pullorum gallinarum only in domestic hens; whereas the infection of gastro-salmonella entertides in all domestic hens, pigeons, turkeys, and ducks was demonstrated, and showed no infection in geese of either kind. Test results also demonstrated positive examined samples of hens, pigeons and ducks only against salmonella typhimurium. The last test was not performed on the other birds. The count of the results of Widal’s reaction for the typhic fever diagnosis in humans showed recording positive cases of 2.6 %. It is deduced thereupon that the presence and living of these birds in the human-animal environment facilitate the opportunity of salmonella’s being transmitted to them with the toxicities and different diseases it causes. Therefore, attention should be centered upon this kind of infection and measures should be taken to prevent it. The recent research plays an important role in this field as well as in tracking and investigating the epidemic process of this disease.